Cross-Lingual Semantic Compatibility of Indonesian and English Concepts of Sensory Perception - Bahri Arifin, M (International Journal of Engineering and Technology, 2018)
This research was conducted to know how Indonesian and English concepts of sensory perception relate to one another in terms of their semantic components and semantic compatibility. The object of the study was the concepts of sensory perception in three sensory channels: auditory, olfactory, and gustatory. The research was designed in qualitative approach with descriptive method of analysis. Data were collected from several printed materials as the main sources i.e. dictionaries, thesaurus, and encyclopedia. The collected data were analyzed by applying componential analysis technique and cross-lingual semantic comparison. The research found that the lexemes used to represent concepts of sensory perception in English were more in number than those used in Indonesian. In terms of semantic components of which the concepts were made up, the research found that the concepts used in both languages were analyzable into a set of semantic components i.e. speech, repeated, crowded, and inherence (auditory-channeled concepts); pleasant, sharp, emanation, and cause (olfactory-channeled concepts); agreeable, acrid, and emphasis (gustatory-channeled concepts). In terms of cross-lingual semantic compatibility, some concepts in either language are mutually translatable with their cross-lingual equivalents in the other language, whereas the rest remain hardly translatable and require circumlocution translation.Â Â